Thymic Medulla Epithelial Cells Acquire Specific Markers by Post-Mitotic Maturation - Penit, Claude (Hindawi Publishing Corporation, 1996)
The development of thymocyte subsets and of the thymic epithelium in SCID and RAG-2(-)/– mice was monitored after normal bone-marrow-cell transfer. The kinetics of thymic reconstitution and their relationships with cell proliferation were investigated by using bromodeoxyuridine to detect DNA-synthesizing cells among lymphoid cells by 3-color flow cytometry, and in epithelial compartments by staining frozen sections. Thymocytes started to express CD8 and CD4 10 days after transfer, simultaneously with extensive proliferation. The first mature CD4(+) single-positive cells were generated, from resting CD4(+)CD8(+) cells after day 15. During this day 10–15 period, many epithelial cells positive for cortexspecific or panepithelial markers were labeled with BrdUrd after pulse-injection. Organized medullary epithelium also developed after day,15, that is, synchronously with the appearance of mature thymocytes, but medullary cells were never found BrdUrd(+). These results suggest that, in these models, the reconstitution of the thymic epithelial network proceeds through expansion of preexisting cortical or undifferentiated cells and by later maturation (acquisition of specific markers) of medullary cells. This last process is dependent of the presence of mature thymocytes.